Practice Exploration and Optimization Path of the Residential College System Reform under the Philosophy of Chinese General Education - Wang, Shijie (Journal of Educational Research and Policies, 2025)
Residential college system reform under the philosophy of general education is an important way to improve the quality of higher education and cultivate comprehensive talents. General education aims to cultivate “complete people” with critical thinking and social responsibility, and promote the improvement of students’ all-round quality through interdisciplinary integration and community learning. Residential college system plays a key role in this process. It provides students with an interdisciplinary learning platform by breaking disciplinary boundaries, strengthening teacher-student interaction, and promoting extensive knowledge. Residential college system and general education’s ideas are highly consistent, especially in terms of educational goals, knowledge breadth, interdisciplinary integration, community-based learning and flexible learning mode. Currently, the residential college system reform faces challenges such as conflicts in management structures, insufficient fulfillment of educational functions, and concerns regarding its legitimacy. Through the practice exploration of Three Chinese University, this paper puts forward some strategies to optimize the reform of residential college system, including clarifying the value of residential college, innovating the curriculum system, reforming the management mechanism, promoting technical support and rooting in traditional culture. The reform of residential college system can not only break through the limitations of traditional education mode, but also provide a strong guarantee for cultivating high-quality talents with global vision and innovative ability.